Quantitative Examination of Dialectal Perception in the Vicinity of the Kaunas Lagoon - Šidlauskas, Žydrūnas (Lietuvių kalba, 2024)
The article analyses two poles of dialectal data: the subjective one (emic) and the objective one(etic). 50 hours of recorded interviews with 52 inhabitants who were evicted from the Nẽmunas valley in the 1950s when the Kaũnas Hydroelectric Power Plant was being built (the Kaũnas Lagoon was formed by flooding the Nẽmunas Valley) are analysed. The article quantitatively reveals the overlap (or no overlap) of data regarding informants, ordinary members of the language community, dialectal perception (emic) and objective (etic) data. This goal was achieved in three steps: 1) based on the features of the reconstructed local dialectal variant of the flooded settlements of the Kaũnas Lagoon, indicators of the dialecticism of the informants were determined; 2) having structured the dialectal perception responses, a quantitative model of dialect awareness was created; 3) having established the correlation between the emic and etic data, an examination of the dialectal perception and the actual usage was carried out on a vertical and horizontal continuum. The collected data shows that the language of the interviewed inhabitants is characterised by the features of the dialectal variant of the southeastern part of Western Aukštaitian of Kaũnas (Priedzūkis); however, only a part of the population considers themselves to be representatives of a dialect. The quantitatively measured level of dialecticism also varies (especially due to intermittent usage). When these indicators of dialecticism were compared with the categorised dialectal perception data, a (paradoxical) reality was determined: there is a mismatch between dialectal perception and actual usage. The mismatch results due to a variety of reasons, one of which is education: informants that have obtained higher education have a better knowledge of the dialect and/or admit it more readily (however, their language is not more dialectal).